PEMETAAN BUDAYA ORGANISASI MENGGUNAKAN ORGANIZATIONAL CULTURE ASSESSMENT INSTRUMENT (OCAI) PADA PT KERETA API INDONESIA DAERAH OPERASIONAL 4 SEMARANG - Umartias, Muhammad; Djastuti, Indi (Faculty of Economics and Business Diponegoro University, 2014)
Transportation is part of the services industry which is needed by people. PT. KAI daop 4 semarang is one of transportation service provider in train sector which always improve and adaptive in order to consumers needs. It has been written in corporate's vision, mission, and five core values hence should be a company working culture. This research aims to conduct cultural mapping current and expected future to be use as input for the company if the current culture and expected according to the value of the company so can make PT KAI Daop 4 Semarang as a company ready to face the changes and demands of consumers This research using the Organizational Culture Assessment Instrument (OCAI) method. The position surveyed is Excecutive Vice President as leader,Â Deputy Excecutive Vice President, Manager, Assistant Manager, and staff with a descriptive quantitative approach so it can be known cultural profile of PT KAI Daop 4 Semarang current and expected future.The results obtained in the study was the difference in the perceived organizational culture at this time by any management position. The dominant culture is currently perceived by Excecutive Vice President is a hierarchy. Perceived dominant culture this time by Deputy Excecutive Vice President is a market. Dominant culture perceived by managers this time is a clan culture. The dominant culture is currently perceived by assistant manager is a adhocracy, and the perceived dominant culture this time by staff is a combination of adhocracy and hierarchy.Then founded the similaritiy of culture which is expected at the level of top management, middle, and bottom are represented by Excecutive Vice President, Manager, and staff is clan culture. While Deputy Excecutive Vice President expects a market culture, and assistant manager expects a adhocracy culture. This cultural profile picture can be use for policy making company according with the company's vision and culture at each position.